Exploring the effects of service quality, shipping cost, brand and attitude on consumer's intentionto choose express courier services in e-commerce - Wiryanta Muljono; Sri Setiyawati (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2019)
The growth of e-commerce has highlighted the importance of express courier service (ECS). We empirically study consumer's choice of ECS in purchasing goods online. This research aims to examine the effect of service quality (SQ), shipping cost, brand, and attitude towards customers' intention to choose ECS on e-commerce. This research was conducted using a quantitative approach among customers who intended their goods to be shipped using ECS. Data of 100 respondents were collected and then analyzed using the structural equation model technique. We find that there is no correlation between SQ and shipping cost and the attitude towards choosing a courier service. However, the analysis indicates that brand has an influence on the customer's attitude towards choosing a courier service. Furthermore, the analysis suggests that the consumer's attitude towards choosing a courier service acts as a mediator between SQ, shipping cost, and brand as regards the consumer's intention to choose an ECS. It is worth noting that brand has a stronger influence on the consumer's attitude compared to the former factors.
Keywords: M39; Y90; 650; service quality; shipping cost; brand; attitude; intentions; express courier service; e-commerce